2013
DOI: 10.1063/1.4827495
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing milestoning networks for molecular kinetics: Definitions, algorithms, and examples

Abstract: Network representations are becoming increasingly popular for analyzing kinetic data from techniques like Milestoning, Markov State Models, and Transition Path Theory. Mapping continuous phase space trajectories into a relatively small number of discrete states helps in visualization of the data and in dissecting complex dynamics to concrete mechanisms. However, not only are molecular networks derived from molecular dynamics simulations growing in number, they are also getting increasingly complex, owing partl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(43 citation statements)
references
References 42 publications
0
43
0
Order By: Relevance
“…25 Previous studies of tryptophan using the more advanced method of milestoning report permeation times on the time scale of hours, which are also in agreement with experimental results. 43,44,85,86 Most other studies have also reported much larger and faster permeability coefficients using the inhomogeneous solubilitydiffusion model, which has been discussed in great detail in other works. 18,25,43,44,[87][88][89] Several assumptions underpin the solubility-diffusion model, including memoryless, diffusivetype motion along the reaction coordinate and the presence of only one slow variable describing the motion of the permeant-namely, the translocation along the membrane normal.…”
Section: Permeability Measuresmentioning
confidence: 98%
“…25 Previous studies of tryptophan using the more advanced method of milestoning report permeation times on the time scale of hours, which are also in agreement with experimental results. 43,44,85,86 Most other studies have also reported much larger and faster permeability coefficients using the inhomogeneous solubilitydiffusion model, which has been discussed in great detail in other works. 18,25,43,44,[87][88][89] Several assumptions underpin the solubility-diffusion model, including memoryless, diffusivetype motion along the reaction coordinate and the presence of only one slow variable describing the motion of the permeant-namely, the translocation along the membrane normal.…”
Section: Permeability Measuresmentioning
confidence: 98%
“…We are interested in conversions of reactants to products and Milestoning is a technique to sample these transitions efficiently. In the past we showed how Milestoning can be used to determine pathways of maximum flux [13]. Here we study another reaction coordinate (the committor).…”
Section: Methodsmentioning
confidence: 99%
“…Examples of methods that provides a one-dimensional view of the reaction progress include the Locally Updated Planes (LUP [8]), Nudged Elastic Band (NEB [9]), and the scalar force [10]. Other approaches are the MaxFlux approach [1113], the String [14], a temperature dependent reaction coordinate [15], and the Dominant Reaction Pathway (DRP [16]). The above approaches provide Minimum Energy Paths, or thermal paths that are locally averaged.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…TPS methods are computationally expensive but they allow, in principle, the computation of both the free energies and rate constants of a process. Other algorithms of similar type include milestoning [86,87], weighted ensemble path sampling [88], and generalizations of the string method [89].…”
Section: Samplingmentioning
confidence: 98%